2015
DOI: 10.1186/s12877-015-0039-7
|View full text |Cite
|
Sign up to set email alerts
|

Does the timed up and go test predict future falls among British community-dwelling older people? Prospective cohort study nested within a randomised controlled trial

Abstract: BackgroundFalling is common among older people. The Timed-Up-and-Go Test (TUG) is recommended as a screening tool for falls but its predictive value has been challenged. The objectives of this study were to examine the ability of TUG to predict future falls and to estimate the optimal cut-off point to identify those with higher risk for future falls.MethodsThis is a prospective cohort study nested within a randomised controlled trial including 259 British community-dwelling older people ≥65 years undergoing us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
112
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(121 citation statements)
references
References 26 publications
2
112
1
6
Order By: Relevance
“…It is unclear what the optimal cut point is. It may vary depending on the outcome and the study population [24,27,28]. We chose to use <10 seconds as this is what was originally described by Podsiadlo et al [6].…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear what the optimal cut point is. It may vary depending on the outcome and the study population [24,27,28]. We chose to use <10 seconds as this is what was originally described by Podsiadlo et al [6].…”
Section: Discussionmentioning
confidence: 99%
“…A survey of 259 elderly people in a British community showed that the TUG's ability to predict future falls was limited and may be more useful in people at high risk for falls rather than as a primary measure in risk assessment [13]. In another study, the authors suggest that TUG is not useful for predicting falls in healthy and active elderly, indicating it for those with impairment in health status and functional capacity [14].…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In fact, nowadays more authors argue that the multifactorial nature of falls requires the development of a comprehensive tool able to accurately detect older adults at risk of falling. 10,12 Consistent with this vision, the construct of frailty has been associated with increased risk of adverse events, such as falls, in older adults. [13][14][15] Frailty is a dynamic and multidimensional condition, defined as a loss of reserve in one or more domains (physical, psychological and social) of individual functioning.…”
Section: Introductionmentioning
confidence: 88%
“…Recently, different studies reported a limited ability of these instruments, used in isolation, to predict falls in older adults . In fact, nowadays more authors argue that the multifactorial nature of falls requires the development of a comprehensive tool able to accurately detect older adults at risk of falling …”
Section: Introductionmentioning
confidence: 99%